Functional importance of an inverted formin C‐terminal tail at morphologically dynamic epithelial junctions. Issue 4 (27th June 2019) - Hegsted, Anna; Votra, SarahBeth; Christophe, Amylisa M.; Yingling, Curtis V.; Sundaramurthy, Sumana; Pruyne, David
Abstract: Epithelial cell–cell junctions have dual roles of accommodating morphological changes in an epithelium, while maintaining cohesion during those changes. An abundance of junction proteins has been identified, but many details on how intercellular junctions respond to morphological changes remain unclear. In Caenorhabditis elegans, the spermatheca is an epithelial sac that repeatedly dilates and constricts to allow ovulation. It is thought that the junctions between spermatheca epithelial cells undergo reversible partial unzipping to allow rapid dilation. Previously, we found that EXC‐6, a C. elegans protein homolog of the human disease‐associated formin INF2, is expressed in the spermatheca and promotes oocyte entry. We show here that EXC‐6 localizes toward the apical aspect of the spermatheca epithelial junctions, and that the EXC‐6‐labeled junction domains "unzip" and dramatically flatten with oocyte entry into the spermatheca. We demonstrate that the C‐terminal tail of EXC‐6 is necessary and sufficient for junction localization. Moreover, expression of the tail alone worsens ovulation defects, suggesting this region not only mediates EXC‐6 localization, but also interacts with other components important for junction remodeling.